(untitled) (Proceedings of the Global Public Health Conference, 2025)
Diabetes mellitus (DM) is the second leading cause of chronic kidney disease (CKD) and related mortality worldwide. Previous reports indicated an increased risk of CKD in the Lao PDR due to poor diet and poor physical activity. The number of patients with CKD has increased, from 4.24% in 2020 to 8.55% in 2022. This cross-sectional study aims to examine factors in self-care behavior among people with type 2 DM who visited three tertiary care hospitals in Lao PDR. The study was conducted at the OPD of these hospitals. Face-to-face interviews were conducted to collect information using structured questionnaires from September to October 2024. A total of 433 subjects completed this study. Descriptive and multiple logistic regression analyses were conducted on the data. Only 41% of respondents demonstrated good self-care behavior. Those who were underweight and normal BMI (AOR: 1.72, 95% CI: 1.12 - 2.65), less knowledge of self-care practices (AOR: 0.49, 95% CI: 0.26-0.93), high perceived severity of CKD (AOR: 2.03, 95% CI: 1.32-3.14), low perceived barriers to performing self-care practices (AOR: 1.71, 95% CI: 1.09-2.69). Based on the findings, it is recommended that CKD prevention among individuals with Type 2 DM be enhanced. Culturally tailored awareness campaigns and health services specifically for high-risk groups are essential. Local healthcare authorities and relevant institutions are encouraged to implement targeted interventions to address these issues effectively. Policymakers and health officials should prioritise improving diabetes care and preventing CKD. Enhancing education about the risks of CKD for individuals with Type 2 DM is crucial. Furthermore, developing risk assessment tools that connect risk perception to health- related behavior could help reduce the burden of CKD and diabetes complications in Laos.